The Janus Corner - Laroo, Hans (Pharmacognosy Communications)
Pharmacognosy is the study of the biological, chemical and physical properties of drugs of crude mixtures or drugs from natural sources. Whilst the majority emphasis in this field is devoted to drugs from plant sources, animal but inorganic derived drugs are also an important sector of the study of pharmacognosy.[1] Just as the search for new drugs from plants requires us to look back to ancient medicinal practices to determine new ways to treating diseases, so too do other areas of our field. Crude inorganic or metallic solutions also have a history of therapeutic usage stretching back many hundreds of years and research into these ancient cures has recently begun to receive renewed attention.[2–5] Colloidal silver pharmaceutical (CSP) preparations in particular